2006
DOI: 10.1074/jbc.m510607200
|View full text |Cite
|
Sign up to set email alerts
|

Single Amino Acid Substitution in the PC1/3 Propeptide Can Induce Significant Modifications of Its Inhibitory Profile toward Its Cognate Enzyme

Abstract: The proprotein convertase PC1/3 is synthesized as a large precursor that undergoes proteolytic processing of the signal peptide, the propeptide and ultimately the COOH-terminal tail, to generate the mature form. The propeptide is essential for protease folding, and, although cleaved by an autocatalytic process, it remains associated with the mature form acting as an auto-inhibitor of PC1/3. To further assess the role of certain residues in its interaction with its cognate enzyme, we performed an alanine scan o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…We estimate that at least 5-10% of the fluorogenic peptide was digested within the analysis period. A similar phenomenon was also observed for the convertase PC1, where the lag phase could last up to 6 h (35).…”
Section: Methodsmentioning
confidence: 56%
“…We estimate that at least 5-10% of the fluorogenic peptide was digested within the analysis period. A similar phenomenon was also observed for the convertase PC1, where the lag phase could last up to 6 h (35).…”
Section: Methodsmentioning
confidence: 56%
“…The inhibitory role of the prodomain is of particular interest to this study when we consider the location of the R80Q (rs1799904) substitution within the secondary cleavage site of the prodomain ( Figure 1 ). Independent studies have shown that alteration of mouse proPC1/3 prodomain residues either within or surrounding cleavage motifs can affect propeptide processing; the in vitro proteolytic conversion of an R80A mutant propeptide (the same residue as the R80Q variant studied here) by wild-type enzyme was impaired compared to wild-type propeptide [44]. Given this finding, our lack of identification of propeptide-bearing R80Q PC1/3 is puzzling.…”
Section: Discussionmentioning
confidence: 72%
“…The proPC1/3 maturation process begins with the autocatalytic intramolecular cleavage of the pro-domain in the ER at the primary cleavage site, RSKR 107–110 [44], [45]. This cleavage yields an 87 kDa form of PC1/3 that, by analogy with the related enzyme furin [46] likely remains associated with its own prodomain through non-covalent interactions until its arrival at the trans-Golgi network.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous regulation of PC1/3 involves the propeptide of PC1/3 and inhibition by proSAAS-derived peptide. The propeptide segment inhibits PC1/3, as well as PC2 and furin (76,77). Furthermore, PC1/3 is inhibited by proSAAS-related peptides (78).…”
Section: Inhibitors and Modulators Of Processing Enzymesmentioning
confidence: 99%